RADIOFREQUENCY ABLATION IN ATRIAL TACHYCARDIA PAROXYSM ON EXAMPLE OF CLINICAL CASE - Brynza, M. S.; Zaporiz’ka, V. V.; Vasylenko, O. A.; Volkov, D. E. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2018)
The disappearance of atrial tachycardia paroxysms after radiofrequency catheter ablation (RFA) of ectopic focus in a left atrium is presented on example of clinical case. Atrial tachycardia paroxysms disappeared after ablation completely. In this case, the RFA of atrial tachycardia was effective. The initial high total power of the HRV spectrum in the patient after ablation decreased by 5 times, but may predict rhythm disturbances in future. In pharmacotherapy, which included cardiomagnil and bisoprolol, the reduction in HRV suggested a gradual increase of the bisoprolol dose.